Listing and protecting culturally significant events: intangible cultural heritage and policy considerations for hockey broadcasting in Canada. Issue 5 (28th July 2020) - Phillips, Ryan J.; Martin, George
ABSTRACT: Listed events are policies enacted by states to protect the free-to-air rights of specific television and radio broadcasts that are identified as being of particular national significance. Some states (including the UK, Belgium, and Argentina) have begun to adopt these listed events policies, typically regarding significant national sporting events. We re-conceptualize listed events as a practical means by which to protect the intangible cultural heritage of states – an issue addressed by international institutions such as ICOMOS and UNESCO. Furthermore, we engage in a critical analysis regarding both the merits and potential problems involved in the possibility of Canada adopting listed broadcasting events policies, specifically involving hockey broadcasts.